METACOGNITIVE STRATEGIES IN ENGLISH READING COMPREHENSION AMONG EFL UNIVERSITY STUDENTS - Heni Novita Sari; Rezzie Fauziyyah (STKIP Paracendekia NW Sumbawa, 2026)
This study explored the university students’ metacognitive strategies used in English reading comprehension. The purpose of this research was to identify the types of metacognitive strategies employed and to understand how these strategies support the university students’ reading comprehension. The study focused on three main categories of global reading strategies, problem-solving strategies, and support reading strategies. This research used a quantitative descriptive method. Data were collected through the Survey of Reading Strategies (SORS) questionnaire and were analyzed descriptively to reveal patterns of strategy used amid university students. The findings showed that university students use the combination of all three strategy types as the problem-solving strategies being the most frequently applied. The university students often relied on rereading, focusing, and translating as the ways of overcoming the reading difficulties. However, global reading strategies such as planning and previewing were less frequent. These results suggested that university students are more likely to use the immediate and practical strategies rather than reflective or planning-based strategies. The study highlighted the need for greater emphasis on balanced strategy training in EFL reading instruction.